2005
DOI: 10.1177/0363546504274145
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Year Follow-up of Patellar Tendon and Hamstring Tendon Grafts for Arthroscopic Anterior Cruciate Ligament Reconstruction

Abstract: Both hamstring and patellar tendon grafts provided good subjective outcomes and objective stability at 7 years. No significant differences in the rate of graft rupture or contralateral anterior cruciate ligament rupture were identified. Patients with patellar tendon grafts had a greater prevalence of osteoarthritis at 7 years after surgery; therefore, the authors preferred hamstring tendons as the primary graft choice in anterior cruciate ligament reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
183
4
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(203 citation statements)
references
References 23 publications
11
183
4
5
Order By: Relevance
“…That is the strength of our study. Numerous studies have been published comparing patellar and hamstring tendon autografts in arthroscopic ACL reconstruction [1,2,5,6,11,18,20]. Many of them have been prospective and randomised, but direct comparison between the grafts was not reliable because fixation techniques, surgical techniques and rehabilitation protocols differed [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is the strength of our study. Numerous studies have been published comparing patellar and hamstring tendon autografts in arthroscopic ACL reconstruction [1,2,5,6,11,18,20]. Many of them have been prospective and randomised, but direct comparison between the grafts was not reliable because fixation techniques, surgical techniques and rehabilitation protocols differed [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…There are few prospective randomised studies on ACL reconstruction directly comparing the outcome of both grafts [1,2,5,6,11,18,20]. The purpose of this prospective, randomised, 5-year follow-up study is to compare the functional results after arthroscopic single-incision ACL reconstruction with patellar tendon or four-strand hamstring tendon autografts, both fixed with interference screws by the same surgeon using the same surgical technique and post-operative rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study, conducted a few years earlier, which included a seven year follow-up, showed significantly higher arthrosis rate in the patellar group, whilst all other parameters were the same. In their conclusion, the authors recommended the hamstrings autograft, although there was a tendency to rupture (not statistically significant) [20]. In their extensive study, Katabi et al [16] emphasise the significantly higher occurrence of femoropatellar pain in the patellar group, but in view of the fact that at the same time knee stability was significantly higher in this patient group, the patellar method is recommended as the gold standard for ACL reconstruction in athletes, especially those practicing pivoting sports.…”
Section: Discussionmentioning
confidence: 87%
“…In the light of harvest site morbidity and postoperative stiffness associated with patellar tendon graft, many surgeons began to choose semitendinosus and gracilis graft [9,16,18]. The actual value of both methods is evaluated in various tests, mostly combining objective measurements and subjective patient opinions [2,20,[23][24][25]. The most commonly used tests are the Single Assessment Numeric Evaluation Score, Lysholm Score, International Knee Documentation Committee Score and Knee Injury and Osteoarthritis Outcome Score [12].…”
Section: Introductionmentioning
confidence: 99%
“…Roe et al [4] reported that ACL reconstruction patients with PT autograft showed higher OA incidence than those with hamstring autograft. However in our study we used a patellar tendon autograft in all cases and we have provided no information about the relationship between OA and graf t choice (PT or hamstring).…”
mentioning
confidence: 99%